Tests of the electroweak sector with precision measurements and diboson final states at the ATLAS Experiment. (August 2020) - Fabbri, L
Abstract: The electroweak sector of the Standard Model can be tested either via precision measurements of fundamental observables or via direct tests of its underlying gauge structure. The ATLAS collaboration has recently released a measurement of the effective leptonic weak mixing angle using data collected at a centre-of-mass energy of 8 TeV. The result has a precision similar to that of the most precise individual measurements. The high integrated luminosity delivered by the LHC during Run-2 has allowed ATLAS to measure integrated and differential cross-sections for several kinematic observable of W ± Z production in pp collisions and to observe vector boson scattering processes with WZ and same-sign WW final states. The results from these milestone analyses as well as their interpretation in the context of the Standard Model are presented in this proceeding.